Sudden justice : America's secret drone wars - Woods, Chris (Journalist) (Nursing History and Humanities MUP., 2015)
"Sudden Justice explores the secretive history of the United States' use of armed drones and their key role not only on today's battlefields, but also in a covert targeted killing project that has let to the deaths of thousands. Days after 9/11, a CIA Predator in Afghanistan executed the world's first lethal drone strike. The Agency's role was no accident -- it had nurtured and developed drones for almost a decade, seeking a platform from which it could monitor its targets and act lethally and instantly on what was learned. Since then remotely piloted aircraft have played a critical role in America's global counter-terrorism operations and have been deployed to devastating effect in conventional wars in Afghanistan, Iraq and Libya. But there is another, covert war -- one in which drones scour the skies of Yemen, Pakistan and Somalia in search of militant and terrorist targets. The American government insists that this secret war is legal. The CIA even claims that its armed drones are "the most precise weapon ever invented," so precise that civilians are no longer killed. Sudden Justice describes the reality of the secret drone war, one in which hundreds of civilians have died, and where the long-term strategic interests of the West may have been jeopardized"--Jacket flap